(untitled) (Tanzania Medical Journal, 2022)
Background Hypertension is a silent killer. Therefore, its early detection and control is very essential. Unfortunately, there is limited information on the hypertension awareness, treatment and control rates in low and lower-middle income countries. Broad Objective This study determined the prevalence of undiagnosed hypertension and hypertension treatment and control rates among adults in Magu district. Methods This was a cross sectional community survey, which enrolled 300 adults. Participants self-reported their socio-demographic characteristics, previous diagnosis of hypertension and current use of antihypertensive drugs. Blood pressure (BP) was measured using aneroid sphygmomanometer. SPSS was used for data analysis. Chi-square or Fisher’s exact tests were used to compare prevalence of hypertension by various factors. Results The overall hypertension prevalence was 29%. Among the hypertensive patients, 78.2 % were not aware of their diagnosis and were thus untreated. Undiagnosed hypertension was associated with increased age, low education level, being employee and family history of hypertension. Among those who were aware of their diagnosis, 63.2% were on medication with only 25% of them having controlled BP. Conclusions and Recommendations Majority of hypertensive patients in rural areas remain undiagnosed and therefore untreated. Among those who are diagnosed, majority of them are either inadequately treated or not treated at all. Therefore, urgent intervention measures are required to avoid morbidity and mortality from potentially preventable complications of hypertension.